Ancient myth on the stage of Kazan theatre - O.O. Nesmelova; E.V. Zueva (Ученые записки Казанского университета: Серия Гуманитарные науки)
This paper considers the history of ancient Greek myths staging in Kazan theatre. The object of research is this process, starting from the 19th century, which let us argue about the diachronic aspect. The ancient Greek mythological plot was always present in the theatre repertoire since the very beginning. For the early times of Kazan theatre, the names of the playwrights are not known. Here, we deal with the transformation of the classical plays. In the 20th century, the myth passes several stages of reception: from the myth itself to its understanding by world-famous playwrights. The personality of the director and actors plays the key role and influences the understanding of classical plots by spectators. It has been concluded that national specifics determine the understanding and staging of well-known plots.